PENGARUH VARIASI NAUNGAN TERHADAP PERTUMBUHAN DAN KONSENTRASI RANTAI PANJANG POLYISOPRENOID SEMAI MANGROVE SEJATI MINOR BERJENIS SEKRESI Xylocarpus granatum (Koenig.) - Try Miharza; Mohammad Basyuni; Yunasfi Yunasfi (Program studi Kehutanan USU, 2015)
X. granatum is one of mangrove plants that may exist in extreme environments. This plant contains secondary metabolites for further study. Complete Random Design (CRD) was used with 5 treatment of light intensity (0%, 25%, 50%, 75% and 100%) of X. granatum seedlings. Results showed that 100% shade (0% light intensity) provided the highest growth response, but does not necessarily provided optimum growth response. The total content of polyisoprenoid in 0% shade was of 0,153 ml little bit higher than 75% of 0.144 ml. TLC analysis of the results showed that the concentrations of dolichol in treatment 0% shade was higher in the root and the leaves of X. granatum seedlings compared to 75% shade treatment . Keywords: Mangrove, Non Saponifiable Lipids ( NSL ), Polyisoprenoid, Xylocarpus granatum.